Antibiotic susceptibility of Pseudomonas aeruginosa in Saudi Arabia: a national antimicrobial resistance surveillance study - Thabit, Abrar K.; Alghamdi, Ammar M.; Miaji, Musaab Y.; Alharbi, Feras S.; Jawah, Anas F.; Alturki, Fatimah; Hosin, Nehal; Bazuqamah, Mohammed; Almutairi, Masaad Saeed; Alhamed, Hamad; Elhendawy, Alaa; Atallah, Dalya; et al. (Frontiers in Public Health, 2024)
Background: Pseudomonas aeruginosa is a common pathogen causing healthcare-associated infections. Most surveillance studies from Saudi Arabia that assessed the resistance by P. aeruginosa were conducted in single centers or did no't use the gold standard test broth microdilution (BMD), the gold standard test. This is the first national multicenter study to assess the resistance profiles of P. aeruginosa isolates in Saudi Arabia using BMD.Methods: Between 2022 and 2023, isolates from various infection sites were collected from 7 seven hospitals from 7in seven different regions of Saudi Arabia. The isolates were shipped to an academic microbiology lab, where their susceptibility was tested by BMD following Clinical Laboratory Standards Institute guidelines using Sensititre GNX3F plates. %sSusceptibility to each antibiotic, as well asand MIC50 and MIC90 were determined.Results: In total, 185 P. aeruginosa isolates were collected. Most isolates came from respiratory specimens (34.1%), followed by urine (21.1%) and skin/soft tissue (17.8%). The greatest highest susceptibility was to amikacin (76.8%). Concurrently, Ssusceptibility to meropenem was 52%, but it was 43.8% to colistin. While all P. aeruginosa isolates met the definition of multidrug-resistance, 41 (22.2%) met the definition ofwere difficult-to-treat and 10 (5.4%) were pandrug-resistant. Difficultto-treat isolates made up 30.3% of skin and soft tissue isolates, 25.4% of respiratory isolates, 21.7% of blood isolates, and 17.9% of urine isolates.P. aeruginosa showed demonstrated an unexpectedly high level of resistance to several commonly used antibiotics. Therefore, Aantimicrobial stewardship and infection control policies should be strictly enforced by hospitals across the country to optimize treatment, prevent the emergence and spread of resistant strains, and track resistance trends with local antibiograms.